Effect of titanium and stainless steel posts in detection of vertical root fractures using NewTom VG cone beam computed tomography system - Mohammadpour, Mahdis (Korean Academy of Oral and Maxillofacial Radiology, 2014)
PURPOSE: Vertical root fracture (VRF) is a common complication in endodontically treated teeth. Considering the poor prognosis of VRF, a reliable and valid detection method is necessary. Cone beam computed tomography (CBCT) has been reported to be a reliable tool for the detection of VRF; however, the presence of metallic intracanal posts can decrease the diagnostic values of CBCT systems. This study evaluated and compared the effects of intracanal stainless steel or titanium posts on the sensitivity, specificity, and accuracy of VRF detection using a NewTom VG CBCT system. MATERIALS AND METHODS: Eighty extracted single-rooted teeth were selected and sectioned at the cemento-enamel junction. The roots were divided into two groups of 40. Root fracture was induced in the test group by using an Instron machine, while the control group was kept intact. Roots were randomly embedded in acrylic blocks and radiographed with the NewTom VG, both with titanium and stainless steel posts and also without posts. Sensitivity, specificity, and accuracy values were calculated as compared to the gold standard. RESULTS: The sensitivity, specificity, and accuracy of VRF diagnosis were significantly lower in teeth with stainless steel and titanium posts than in those without posts. Interobserver agreement was the highest in teeth without posts, followed by stainless steel posts, and then titanium posts. CONCLUSION: Intracanal posts significantly decreased the VRF diagnostic values of CBCT. The stainless steel posts decreased the diagnostic values more than the titanium posts.